Effect of NaCl Concentration on Microbiological Properties in NaCl Assistant Anaerobic Fermentation: Hydrolase Activity and Microbial Community Distribution - Pang, Heliang; Xin, Xiaodong; He, Junguo; Cui, Baihui; Guo, Dabin; Liu, Shiming; Yan, Zhongsen; Liu, Chong; Wang, Xinyu; Nan, Jun (Frontiers in Microbiology, 2020)
Previous studies have demonstrated that sludge hydrolysis and short-chain fatty acids (SCFAs) production were improved through NaCl assistant anaerobic fermentation. However, the effect of NaCl concentrations on hydrolase activity and microbial community structure was rarely reported. In this study, it was found that α-glucosidase activity and some carbohydrate-degrading bacteria were inhibited in NaCl tests, owing to their vulnerability to high NaCl concentration. Correspondingly, the microbial community richness and diversity were reduced compared with the control test, while the evenness was not affected by NaCl concentration. By contrast, the protease activity was increased in the presence of NaCl, and reached the highest activity at the NaCl concentration of 20 g/L. The protein-degrading and SCFAs-producing bacteria (e.g. Clostridium algidicarnis, Proteiniclasticum) were enriched in the presence of NaCl, which were salt-tolerant.